ANALISIS FINANSIAL DAN EKONOMI TANAMAN SELA JAGUNG DAN KEDELAI PADA TANAMAN KELAPA SAWIT BELUM MENGHASILKAN - Muhammad Akmal Agustira; Ilham Lubis; Eka Listia; Erwin Nyak Akoeb; Iman Yani Harahap; M. Edwin S. Lubis (Pusat Penelitian Kelapa Sawit, 2018)
Maize and soybean can be planted for intercropping on immature oil palm, however its financial and economycal aspects have not been widely studied. This study was aimed to analyze the financial and economic aspects of intercropping of maize and soybean on immature oil palm, level of land use efficiency, and comparison of efficiency between monolculture and intercropping system. The study located in Sorolangun Experimental Station, District of Sorolangun, Jambi. Methods used in the study were farming business analysis, Revenue Cost Ratio (RCR), Return on Investments (ROI), Land Equivalent Ratio (LER), and Land Equivalent Optimize Ratio (LOER). The results showed that maize had a profit level of Rp 9,676,564/ha/growing season, RCR 1.76; ROI 188.28% (three growing seasons per year), while soybean had a profit level of Rp 4,059,352/ha/growing season, RCR 1.51 and ROI 75.22% (three growing seasons per year). Based on these results, intercropping of maize and soybean on immature oil palm are economically and financially feasible. For the land use efficiency, corn LER value for corn and soybean was 0.95 and 0.85, respectively, showing that yield of maize and soybean from intercropping system (effective land area of ​​7,200 m2 per ha of oil palm area) was 95% and 85% when compared to monoculture system. The LOER value of corn and soybeans per ha was 1.32 and 1.18, respectively, which showed that corn and soybeans growing on intercropping system with immature oil palm were more efficient than monoculture system at the same size of land. Based on those comparative analysis of economic values, financial, and land use efficiency, corn was a better alternative crop for intercorpping on immature oil palm than soybean.